IN VITRO IMMUNOTROPICITY STUDIES OF POLYFUNCTIONAL WATER-SOLUBLE ANTIOXIDANTS - S. Yu. Klepikova; O. P. Kolesnikova; A. Ye. Prossenko; N. V. Kandalintceva (Медицинская иммунология, 2014)
Abstract. A study of immunotropic properties of ω-(3,5-dimethyl-4-hydroxyphenyl) propylthiosulfonate, sodium salt (F-11-7), and ω-(3,5-di-tret-butil-4-hydroxyphenyl) propylthiosulfonate, sodium salt (F-17-7) was carried out, employing an in vitro model of spontaneous and mitogen- stimulated proliferation of cultured spleen cells. It is revealed, that the F-11-7 and F-17-7 compounds are able to suppress proliferation of intact splenocytes in a dose-dependent manner. (Med. Immunol., 2008, vol. 10, n 2-3, pp 269-272).